Does Profitability Matter in the Relationship between Intellectual Capital and Firm Value? - Thapenes Roy Appah; Sari Yuniarti; Nanik Sisharini; Sunarjo Sunarjo; Nurhidayah Yahya (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2023)
A study of intellectual capital was conducted to determine whether it can predict firm value by moderated ROA. This study is a quantitative study using secondary data from 240 observational datasets. Purposive sampling selection with company criteria in the LQ-45 index is used as a selection method consecutively from 2017 to 2020. The method of data analysis was panel data regression and Moderated Regression Analysis. The best estimation model used is the Fixed Effect model. We find that intellectual capital predicts the firm value. We also investigated that value-added capital employed and structural capital value added had a significant effect on firm value. In contrast, value-added human capital had no effect on firm value. We prove that profitability moderates the relationship between intellectual capital and firm value. The findings reveal that intellectual capital is an important determinant of a firm's value, thus the company of the LQ-45 index in developing economies like Indonesia needs to enhance their intellectual potential. Therefore, companies must stimulate the growth of capital employed and the efficiency of structural capital for enhanced firm value by strengthening ROA performance. This allows managers to allocate resources to critical knowledge assets for intellectual capital that can be turned into a sustainable competitive advantage.